Job Insecurity dengan Komitmen Organisasi pada Karyawan di Kabupaten Lima Puluh, Kota Payakumbuh - Natura, Belly; Fitri, Nur Azizah (Psyche 165 Journal, 2023)
Human resources are the most important asset for the company in the digitalization era, so companies need to manage them optimally so that every employee is able to show superior performance and high commitment to an organization, but there are several influencing factors that can make an employee's organizational commitment low. This study aims to determine the relationship between job insecurity and organizational commitment on contract employees of PT XYZ. The independent variable in this study is job insecurity and the dependent variable is organizational commitment. The measuring instrument used in this research is the scale of job insecurity and organizational commitment sampling technique in this study used a non-probability sampling technique, namely the saturated sample in this study were 38 contract employees of PT XYZ. Test the validity and reliability in this study using the Alpha Cronbach. The results of the validity coefficient on the job insecurity move from rix = 0.576 to rix = 0.682 with a reliability coefficient of = 0.940 while the organizational commitment scale moves from rix = 0.530 to rix = 0.690 with a reliability coefficient of = 0.934. Based on data analysis, the correlation value is -0.769 with a significance level of 0.000, which means that the hypothesis is accepted. This shows that there is a negative and significant relationship between job insecurity and organizational commitment on contract employees of PT XYZ. Meaning that to increase organizational commitment it is necessary to reduce job insecurity on employees at PT XYZ. The contribution of the job insecurity to organizational commitment is 59.1%.